PEMENUHAN HAK MEMILIH DAN MEMPEROLEH AKSESIBILITAS SEBAGAI HAK POLITIK PENYANDANG DISABILITAS OLEH KPUD KABUPATEN KARANGANYAR PADA PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2024 DI KECAMATAN JATIPURO - Ramadhani, Nabila; Permata H, Rima Vien; Hendri N, Muhammad (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2025)
The purpose of this study is to analyze efforts and describe factors that influence the right to vote and obtain accessibility as political rights for people with disabilities by the Karanganyar Regency KPUD in the 2024 Presidential and Vice Presidential Election in Jatipuro District. This study is a qualitative study with a case study approach regarding the phenomenon of low voter turnout for people with disabilities in Jatipuro District. Data were obtained through interviews, observations, and supporting documents. The results of this study are efforts to provide voting rights and obtain accessibility for voters with disabilities are carried out by registering as voters, conducting socialization for voters with disabilities, conducting technical guidance for Pantarlih and KPPS, and realizing accessibility through mobile ballot box services. However, these efforts have not been maximized because there are no rules that serve as guidelines in determining the ability to vote, there are limitations in time, budget, and personnel in socialization, the workload of KPPS is quite heavy in a short working time causing psychological pressure that has an impact on fatigue and lack of focus, and the geographical conditions of Jatipuro District which cause several TPSs to not yet be accessible to voters with disabilities. Keywords: Right to Vote, Accessibility, Disability Awareness, Regency KPUD, General Election